Desarrollo de la geometría en niños de 4 años y nivel de instrucción materna (Investigaciones) - Garzón Picón, Daniela Anabel (2026)
International studies have shown that early geometric development predicts future mathematical performance. However, the level of geometric performance of young children and its possible association with maternal educational attainment are unknown in the country. Therefore, the objectives of this study were to determine the level of development of geometric skills of 4-yearold children, and to analyze if there is a relationship between the level of maternal instruction and children’s geometric performance. For this, a quantitative approach with a descriptive and correlational scope was used, with the participation of 60 preschool children of Cuenca. Children’s level of geometric development was evaluated using the Tools for early mathematical assessment test and the Spatial thinking test. Data on the level of maternal instruction were obtained from the socioeconomic records filed in each school. The results indicated that the children have low geometric performance with large individual differences in that performance. In addition, the level of maternal instruction was not correlated with the children’s geometric skills. From the educational point of view, these results point to the need to implement educational interventions that stimulate essential geometric skills in Ecuadorian preschool classrooms.